Ethics of germline genome editing to prevent genetic diseases from an Islamic perspective - Muhsin, Sayyed Mohamed; Chin, Alexis Heng Boon (Progress Educational Trust (PET), 2024)
In 2018, Dr He Jiankui announced he created the world's first genome-edited babies (BioNews 977), which sparked a call for a five-year moratorium on germline genome editing. As this moratorium ends, it is timely to ask how do we progress from here?